RESPONSIVITAS DALAM PENDAFTARAN PERALIHAN HAK ATAS TANAH JUAL BELI DI KANTOR PERTANAHAN KABUPATEN SIGI ROVINSI SULAWESI TENGAH - Wowor, Steven Octovia Kennedy (Katalogis, 2016)
The Registration Responsivitas Switchover of Land right Sales in Land Ground Office  Sigi Regency of Central Sulawesi Province This Research Target is to know and analyse the Registration Responsivitas of Switchover  Land right Sales Office Land; Ground Sigi Regency of  Central Sulawesi Province. Theory used by that is theory of Agus Dwiyanto (2006) consisted of: (1) Service User Sigh, (2) Officer Attitude (3) Repair Reference (4) Officer action and (5) Service User Location. This Research Type is research qualitative with the informan selected  by the five of people. Data collecting use the technique interview and documentation. Technique analyse the data used by that is (1) Data Collecting  (2) Data Reduction  (3) Data Presentation (4) Verification and  (5) Conclusion.  Result  Research is:   Responsivitas in registration  Switchover of Land right  Sales in office  Land;Ground Sigi Regency of  Central Sulawesi Province.not yet walked better, with the detail: Responsivitas in registration Switchover  Land right Sales in office  Land Ground  Sigi Regency of  Central Sulawesi Province. seen from factor of service user sigh, officer attitude, reference of repair and officer action not yet walked better. This matter is seen from time duration still in getting land;ground certificate and result of interview with the informan. Later;Then Responsivitas in registration of Switchover  Land right Sales in office  Land;Ground Sigi Regency of  Central Sulawesi Province.  seen from factor of location  service user have walked better. This matter is seen from medium and prasarana which is reserved for by location of service user and also from result interview with informan.